Rab35 GTPase recruits NPD52 to autophagy targets. (28th August 2017) - Minowa‐Nozawa, Atsuko; Nozawa, Takashi; Okamoto‐Furuta, Keiko; Kohda, Haruyasu; Nakagawa, Ichiro
Abstract: Autophagy targets intracellular molecules, damaged organelles, and invading pathogens for degradation in lysosomes. Recent studies have identified autophagy receptors that facilitate this process by binding to ubiquitinated targets, including NDP52. Here, we demonstrate that the small guanosine triphosphatase Rab35 directs NDP52 to the corresponding targets of multiple forms of autophagy. The active GTP‐bound form of Rab35 accumulates on bacteria‐containing endosomes, and Rab35 directly binds and recruits NDP52 to internalized bacteria. Additionally, Rab35 promotes interaction of NDP52 with ubiquitin. This process is inhibited by TBC1D10A, a GAP that inactivates Rab35, but stimulated by autophagic activation via TBK1 kinase, which associates with NDP52. Rab35, TBC1D10A, and TBK1 regulate NDP52 recruitment to damaged mitochondria and to autophagosomes to promote mitophagy and maturation of autophagosomes, respectively. We propose that Rab35‐GTP is a critical regulator of autophagy through recruiting autophagy receptor NDP52. Synopsis: GTPase Rab35 directs autophagy receptor NDP52 recruitment to ubiquitinated targets, thereby facilitating xenophagy, mitophagy and autophagosome maturation. GTP‐bound active Rab35 accumulates on bacteria‐containing endosomes and recruits NDP52 in a TBK1‐dependent manner. Rab35‐GTP directly interacts with NDP52 and facilitates its binding to ubiquitin to promote xenophagy. Rab35‐mediated NDP52 recruitment to bacteria is inhibited by TBC1D10A through inactivation of Rab35. Rab35‐mediated NDP52 targeting to damaged mitochondria and autophagosomes facilitates mitophagy and autophagosome maturation, respectively. Abstract : GTPase Rab35 directs autophagy receptor NDP52 recruitment to ubiquitinated targets, thereby facilitating xenophagy, mitophagy and autophagosome maturation.